(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Roesma DI, Tjong DH, Janra MN, Aidil DR. 2022. DNA barcoding of freshwater fish in Siberut Island, Mentawai Archipelago, Indonesia. Biodiversitas 23: 1795-1806. Information regarding molecular data of freshwater fish in Siberut Island, Mentawai Archipelago, Indonesia, is not available. This study was conducted to provide DNA barcodes of freshwater fish in Siberut island. The cytochrome oxidase subunit 1 (COI) gene was chosen to make DNA barcodes because it has been used as a tool capable of identifying organisms up to the species level. Specimens were collected directly captured in the three rivers from Siberut Island. A total of 40 individuals were selected from 200 individuals that have been identified morphologically and strengthened by the results of the molecular marker (DNA barcodes) consisting of 13 species, namely Gobiopterus cf. brachypterus (BOLD: ADF5945), Eleotris fusca (BOLD: AAF0108), Butis cf. butis (BOLD: AAL8960), Stiphodon semoni (BOLD: ACQ3312), Giuris margaritacea (BOLD: ACP9929), Anabas testudineus (BOLD: AAO2846), Rasbora jacobsoni, Rasbora vulcanus, Barbodes banksi, Redigobius cf. bikolanus, Periophthalmus argentilineatus, Hypseleotris cf. compressa, and Oryzias cf. javanicus (in a queue in the BOLD system). The average Kimura two-Parameter model (K2P) genetic distances within species, genera, families, and orders were 0.16%, 11.4%, 23.2%, and 26.0%, respectively. The interspecific K2P distance was higher than the intraspecific distance. The present study supports that COI Barcodes effectively identify fish up to the species level. Future research is needed, especially to species that may have potential as new species. In contrast, DNA barcodes as genetic information will contribute as the basic data to future studies in the monitoring, conservation, and management of freshwater fish in Siberut Island, Mentawai Islands. Therefore, the creation of DNA barcodes is immediately carried out.